PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN PENGGUNAAN DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN ARTIFICIAL INTELLIGENCE LILY BANK J TRUST - Lina, Lina (Catholic University Musi Charitas, 2020)
The purpose of this study was to determine the effect of perceived usefulness, perception of ease of use and trust in interest of using the Virtual Assistant Lily Bank J Trust. The population of this research is the people who use the virtual assistant Lily Bank J Trust. This type of research is survey research. Data collection techniques are surveys by distributing questionnaires developed from previous research. The sampling technique used purposive sampling with 115 respondents. Multiple regression analysis was used to examine the effect of perceived usefulness, perceived ease of use and trust in the interest of using Lily Bank J Trust's virtual assistant. The results showed the magnitude of the influence of the effect of perceived usefulness, perceived ease of use and trust in the interest of using the virtual assistant Lily Bank J Trust by 53.6% while 46.4% was influenced by other variables outside this study, including government policy variables, advertising socialization, and so on.